Interaction of drought stress and potassium deficiency on soybean vigor and leaf temperature - C. C. Ortel; T. L. Roberts; L. C. Purcell; W. J. Ross; K. A. Hoegenauer; C. A. Followell; M. Victorio Pessotto (Agrosystems, Geosciences & Environment)
Abstract Potassium (K) nutrition and drought stress affect soybean (Glycine max (L.) Merr.) vigor and productivity through the combined impacts on water regulation. A study was conducted with soybean grown in 18.9‐L buckets under a rain out shelter to determine how the interaction between these crop stresses at various growth stages influences the crop leaf K concentration, biomass production, total K uptake (TKU), grain yield, and temperature of the uppermost fully expanded trifoliate. Treatments included soybean grown with and without preplant fertilizer K, soil moisture at 50% (drought) or 80% (well‐watered) field capacity, imposed drought during vegetative growth (V3–V7), flowering (R1–R3), pod development (R4–early R6), and seed development (R5–mid‐R6) on two different silt loam soils. Widespread K deficiencies were observed during the study across all treatments. Drought stress significantly (p < 0.05) reduced the TKU, aboveground biomass production, and grain yield. The crop growth stage when drought stress was imposed was a significant factor, with greater reductions in plant response parameters when stress was imposed during reproductive growth. Preplant fertilizer K increased trifoliolate K concentrations and TKU in drought conditions, but did not increase the grain yield of well‐watered soybean. Leaf temperature increased when under drought stress compared to well‐watered soybean (p < 0.0001) but the impact of crop K nutrition status on leaf temperature was inconclusive because of widespread K deficiencies. Results emphasize the complexity of the interactions between K nutrition and drought stress in soybean, as drought stress impeded K uptake, exacerbated K deficiencies, and limited yield.